Effective time of surgery of the third mandibular molar and difficulty factors - Vasquez Vasquez, Maria (2012)
Objective: To determine the relationship between effective time of surgery, with the factors of difficulty for the extraction of mandibular third molar. Materials and Methods: The study was descriptive. 30 extractions were evaluated by a maxillofacial surgeon. The parameters taken were: space, depth, spatial relationships, size of the follicle, and the integrity of bone and y mucosa, and form roots. We calculated the frequencies of the variables and covariates. It continues with a bivariate analysis using Pearson correlation coefficients, relating the time with all the variables. Results: The average time of third molar extraction was 9.63 min. It was found more frequently Class II, Level B, mesioangular position, size of follicle from 0 - 1 mm., completely covered by mucosa and partly by bone and the most common form of the roots were 2 / 3 combined and more than 2 / 3 apart. Conclusions: effective time of surgery is related significantly with size of the follicle, the integrity of bone and mucosa and depth. The available space, spatial relationships and form roots were not significant. There is a direct relationship between the effective time of surgery and age.